New insights into Li distribution in the superionic argyrodite Li6PS5Cl. Issue 82 (30th September 2021) - Zhao, Enyue; He, Lunhua; Zhang, Zhigang; Doux, Jean-Marie; Tan, Darren H. S.; Wu, Erik A.; Deysher, Grayson; Chen, Yu-Ting; Zhao, Jinkui; Wang, Fangwei; Meng, Ying Shirley
Abstract : A previously unreported Li lattice site was discovered in the argyrodite solid-state electrolyte, completing the Li diffusion model in argyrodites. Abstract : By using temperature-dependent neutron powder diffraction combined with maximum entropy method analysis, a previously unreported Li lattice site was discovered in the argyrodite Li6 PS5 Cl solid-state electrolyte. This new finding enables a more complete description of the Li diffusion model in argyrodites, providing structural guidance for designing novel high-conductivity solid-state electrolytes.